FEATURES OF FOREIGN EXPERIENCE STATE SUPPORT FOR AGRICULTURE AND ITS APPLICATION IN RUSSIA - S. Gorlov; G. Panaedova; A. Borodin (Вестник Северо-Кавказского федерального университета)
The article analyzed foreign experience of state support for agriculture from the point of view of its possibility of application in the Russian Federation in modern economic conditions. The authors reveal the practice of the most effectively used tools to support the industry in the EU, USA, China. On the basis ofnew s statistical data, the effectiveness of measures of state support for agriculture has been studied and measures of potential instruments of state support for domestic agricultural producers have been justified.